Taboo Language in Daily Conversations of English Education Students at HKBP Nommensen University - Tampubolon, Sahlan; Fritz Ogest Malau, Aroon; Susanti, Susanti (ELS Journal on Interdisciplinary Studies in Humanities, 2026)
This study aims to identify the types of Indonesian taboo language used by fifth-semester students of the English Education Study Program at HKBP Nommensen University and to analyze the contextual factors influencing their use in daily conversations. Taboo language frequently appears in informal communication and reflects social interaction patterns among students. This research employed a descriptive qualitative method. The data were collected through natural observation and audio recordings of students’ conversations around the ground floor area of Building L at HKBP Nommensen University. A total of 193 taboo expressions were identified from 35 speech events. The data were analyzed using the classification of taboo language proposed by Edwin L. Battistella, while the contextual analysis was interpreted through the SPEAKING model developed by Dell Hymes. The findings reveal that epithets are the most frequently used type of taboo language in students’ conversations. These expressions are commonly used in informal interactions to express emotions, humor, and solidarity among peers. The study indicates that taboo language in this context functions not only as offensive language but also as a strategy for maintaining social bonding among students.